Application of the Lome IV Convention to services and the potential opportunities for the Barbados international financial sector. - Zagaris, Bruce (1992)
Discusses the structure and main features of the Convention. Considers the provisions on services, and calls for strengthening financial services such as insurance and credit institutions in trade development and promotion. Asserts that under the Convention, attention should be paid to strengthening the capacity of the ACP states such as Barbados in financial services.